Chronic relapsing homologous collagen-induced arthritis in DBA/1 mice as a model for testing disease-modifying and remission-inducing therapies. - Malfait, A; Williams, R; Malik, A; Maini, R; Feldmann, M (2001)
OBJECTIVE: To test whether the chronic relapsing arthritis induced by immunizing DBA/1 mice with homologous type II collagen is a valuable model for testing disease-modifying antiarthritic drugs. METHODS: Six-week-old male DBA/1 mice were immunized with murine type II collagen in Freund's complete adjuvant, resulting in a chronic relapsing polyarthritis in >80% of the mice 4 weeks after immunization. At the onset of clinical arthritis, mice were treated for 4 weeks with different treatments, including anti-tumor necrosis factor (anti-TNF) and antiinterleukin-12 (anti-IL-12) antibodies, salbutamol, or indomethacin. Alternatively, treatment was administered as a pulse at the beginning of clinical arthritis. Pulse treatments tested included anti-CD3 in combination with anti-TNF, anti-TNF alone, and anti-CD4, either alone or in combination with anti-TNF. After 4 weeks of arthritis, mice were killed and hind paws were assessed histologically for joint damage. RESULTS: Anti-TNF and salbutamol both suppressed clinical arthritis more effectively than indomethacin and, moreover, protected the joints from damage, whereas indomethacin did not. Anti-IL-12 treatment initiated after the onset of clinical symptoms accelerated disease. Pulse therapy with anti-CD3 plus anti-TNF was found to induce remission, clinically as well as histologically, whereas a pulse with either anti-CD4, anti-TNF, or the combination of anti-CD4 plus anti-TNF was less effective. CONCLUSION: Chronic relapsing homologous collagen-induced arthritis is a valuable model for identifying remission-inducing antiarthritic drugs and has predictive value with respect to their joint-protective potency.